2011
DOI: 10.1589/jpts.23.205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hip Muscle Strength and Kinematics of the Knee Joint during Single Leg Squatting and Dropping

Abstract: Abstract.[Purpose] The aim of this study was to determine relationship between hip muscle strength and kinematics of the knee joint during single leg squatting and dropping.[Subjects] Twelve healthy subjects participated in this study.[Methods] The knee medial displacement was measured during single leg squatting and dropping using a highspeed camera. Peak isometric muscle strengths of the following muscles were measured hip abductors, hip adductors, hip external rotators, hip internal rotators, knee extensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…There was an overall lack of evidence for the relationship between maximal hip muscle strength (especially abduction and extension) and test performance [143,169,173,175,179,184,185,191,192,[194][195][196]. Only hip external rotation strength was found to have strong evidence of relationship with test outcome (frontal plane knee movement) during the SLSQUAT test [143,184,185,192,195].…”
Section: Validity Of Clinical Tests Of the Lumbo-pelvic-hip Complexmentioning
confidence: 97%
See 4 more Smart Citations
“…There was an overall lack of evidence for the relationship between maximal hip muscle strength (especially abduction and extension) and test performance [143,169,173,175,179,184,185,191,192,[194][195][196]. Only hip external rotation strength was found to have strong evidence of relationship with test outcome (frontal plane knee movement) during the SLSQUAT test [143,184,185,192,195].…”
Section: Validity Of Clinical Tests Of the Lumbo-pelvic-hip Complexmentioning
confidence: 97%
“…Evidence of correlation between maximal hip abduction strength and frontal plane knee kinematics was conflicting. Although most studies showed no relationship [143,169,185,191,192,194,195], three showed low to moderate correlations between hip abduction strength and knee valgus movement [184,185,195]. Conflicting evidence was found for correlations between hip abduction strength and hip adduction angle (negligible non-significant correlations in one study, moderate negative correlations in another) [173,184].…”
Section: Slsquatmentioning
confidence: 97%
See 3 more Smart Citations